Dynamics of a Fifth-Order Iterative Method - Plaza, S (TAYLOR & FRANCIS LTD, 2012)
In this paper, we study the dynamical behaviour of a two-point iterative method with order of convergence five to solve nonlinear equations in the complex plane. In fact, we complement the dynamical study started in previous works with a more systematic analysis for polynomials with at most two different roots and different multiplicities. In addition, we characterize some polynomials of degree greater or equal to 4, such that the related methods are not generally convergent. We also analyse the degrees of the rational functions associated with two-point methods when they are applied to polynomials of degree n, showing their dependence on n2 and how this fact considerably complicates the dynamical study. © 2012 Copyright Taylor and Francis Group, LLC.
Keywords: general convergence; nonlinear equations; iterative processes; Julia sets; order of convergence